Traveling the old ski tracks of New England - Allen, E. John B., 1933- (Bright Leaf, an imprint of University of Massachusetts Press, 2022)
"For over a century New Englanders have taken to the slopes in search of ways to enjoy the coldest months, and skiing has deep roots in the region. In the late nineteenth century Scandinavian immigrants worked to educate snowbound locals on how to ski, make equipment, and prepare trails. Soon thereafter, colleges across the Northeast built world-class ski programs, massive jumps were constructed in Brattleboro and Berlin, and dozens of ski areas-big and small-cropped up from the 1930s through the 1960s. Traveling the Old Ski Tracks of New England offers a fascinating history of downhill, cross-country, and backcountry skiing across the region and its leading personalities. Moving from popular destinations like Stowe, Cannon, Bromley, and Mount Washington to the less intimidating hills surrounding Boston, Rhode Island, and Connecticut, E. John B. Allen also recovers the forgotten stories of ski areas that have been abandoned in the face of changing tastes and a warming climate"--